Student Recruitment Management Strategy In School - Adinda Suciyandhani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the strategy for recruiting education in schools, one of which is teachers, because the quality of educational staff in schools is very dependent on the recruitment and selection strategy for interested applicants and in order to be able to find new employees who are professional and have the best quality abilities. Before carrying out the recruitment activities for these educators, they must be thoroughly mature so that they can go through the educational recruitment process at schools as professional educators according to school criteria because it will have an impact on students. This research method uses this type of qualitative research with library analysis techniques. Management functions to achieve something through the activities of other people and supervise individual efforts to achieve common goals. As for the management functions of planning (Planning), organizing (organizing), directing (actuating), and controlling (controling). The focus of the research in this research is, 1) How is the recruitment strategy, How is the implementation of recruitment, What are the implications of implementing recruitment in improving the quality of students.